Many faces of dismantling: hiding policy change in non-legislative acts in EU environmental policy. Issue 1 (2nd January 2020) - Pollex, Jan; Lenschow, Andrea
ABSTRACT: Research on the termination or reduction of policies under the header of policy dismantling is becoming increasingly relevant within public policy analysis. To foster the understanding of dismantling this paper proposes to analyse post-legislative measures defining the setting of policy instruments and to look closely into how this phase provides room and opportunities for dismantling attempts. We investigate dismantling in EU sustainable consumption policy and concentrate on measures implementing the two major instruments in this area: the command-and-control ecodesign policy aiming at producers and the soft information instrument ecolabel aiming at consumers. While the legislative development of the two policies shows no sign of dismantling along the dimensions of policy intensity and density, investigating the respective implementation measures in three crucial product groups of electronic equipment the analysis points to a change in the instrument setting. Thus, the cases studied suggest that the dismantling research benefits from in-depth policy research uncover dismantling strategies that easily remain hidden from political attention.